PENGEMBANGAN MAHARATUL KALAM BERBASIS DIGITAL DI MA PALAPA NUSANTARA NW LOMBOK - Ali Fathurrahman; Baiq Raudatussolihah; Masita Taufiqi Kholida (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2025)
AbstractDeveloping maharatul kalam (the ability to speak Arabic) is very important in the digital era to form individual students who are able to communicate effectively in local and global contexts. This research aims to analyze the approaches, methods and implications of developing digital-based maharatul kalam at MA Palapa Nusantara NW Lombok. This research uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews and document study. The research results show that communicative and technology-based approaches have a significant influence in improving students' speaking skills. Methods such as role play, online discussions, and the use of Arabic learning applications are effective in motivating students to be more active and confident in speaking. In addition, digital technology allows students to study independently through online platforms, such as YouTube, Zoom, and language learning applications. The implication of this research is the need to integrate technology in the Arabic language learning curriculum and strengthen students' digital literacy. With the right approach and methods, developing maharatul kalam not only improves students' speaking skills, but also forms a generation that is adaptive and competent in facing global challenges.Keywords: Development, Maharatul Kalam and Digital Based.